Inclusive Human Resource Management Practice to Change The Organizational Climate - Rizky, Ulfah Fatmala (Indonesian Journal of Disability Studies, 2021)
This study aims to describe and analyze the organizational climate change process in Mandiri Contact Center (MCC) Yogyakarta which employs people with disabilities since the implementation of the Mandiri Kriya Difabel Program. A qualitative method with an instrumental case study approach is used in this study. To collect the data, the researcher uses interview, observation and documentation study technique. The results show that by implementing an inclusive human resource management, the Mandiri Kriya Difabel Program has succeeded to change an exclusive organizational climate into an inclusive disability organizational climate. This is the first study which combines Lewin's Three Step Change Model, Social Model of Disability, and Inclusive Dimensions on Organizational Climate as a framework to research a disability inclusive organizational climate change. This research provides an inclusive method to manage employees with disabilities and a new academic reference on organizational change study.